2020
DOI: 10.3389/fvets.2020.00452
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Chicken Lungs Infected With Avian and Bovine Pasteurella multocida Serotype A

Abstract: Pasteurella multocida (P. multocida) is a common animal pathogen responsible for many animal diseases. Strains from different hosts exhibit disparate degrees of effect in other species. Here, we characterize an avian P. multocida serogroup A strain (PmQ) showing high lethality to chickens and a bovine P. multocida serogroup A strain (PmCQ2) with no lethality to chickens. We used RNA-seq to profile the transcriptomes of chicken lungs infected with PmQ and PmCQ2. A total of 1,649 differentially expressed genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…The study on genomic analysis of a highly virulent P. multocida strain PmCQ2 induced host response suggested that PmCQ2 infection may activate NOD-like receptor signaling pathway ( Wu et al, 2017 ; Li et al, 2020 ; He et al, 2021 ). The central protein of the inflammasome complex include NOD-like receptor (NLR) family, AIM2-like receptor (ALR) family, and pyrin protein.…”
Section: Introductionmentioning
confidence: 99%
“…The study on genomic analysis of a highly virulent P. multocida strain PmCQ2 induced host response suggested that PmCQ2 infection may activate NOD-like receptor signaling pathway ( Wu et al, 2017 ; Li et al, 2020 ; He et al, 2021 ). The central protein of the inflammasome complex include NOD-like receptor (NLR) family, AIM2-like receptor (ALR) family, and pyrin protein.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, various papers have demonstrated that AA has an impact on macrophage function, and macrophages played a vital role during P. multocida infection (48). For instance, intracellular accumulation of pharmacologic AA concentrations in human monocytes inhibited its apoptosis pathway activation (49).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 4A , supplementation with AA significantly reduced the lung bacterial density while supplementation with Asp only has an upward trend on lung bacterial density. Additionally, various papers have demonstrated that AA has an impact on macrophage function, and macrophages played a vital role during P. multocida infection ( 48 ). For instance, intracellular accumulation of pharmacologic AA concentrations in human monocytes inhibited its apoptosis pathway activation ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several of these DEGs [e.g., interleukin-1beta (IL-1β), interleukin 4-induced 1 (IL4I1), interleukin 1 receptor type 2 (IL1R2), IL-22, and suppressor of cytokine signaling 3 (SOCS3) cytokines] showed the same expression trend and were upregulated in P. multocida -infected lungs of goats and those of chicken. Through an analysis of the enriched KEGG pathways, we found that many of these same DEGs are involved in the p53 signaling pathway and cytokine–cytokine receptor interactions ( 33 ). The most enriched KEGG pathway cytokine–cytokine receptor interaction was also enriched by the mouse lung DGEs that infected with P. multocida ( 31 ).…”
Section: Discussionmentioning
confidence: 99%